Metabolomics-Driven Elucidation of Cellular Nitrate Tolerance Reveals Ascorbic Acid Prevents Nitroglycerin-Induced Inactivation of Xanthine Oxidase - Axton, Elizabeth Rose; Cristobal, Eleonso; Choi, Jaewoo; Miranda, Cristobal L.; Stevens, Jan Frederik (Frontiers in Pharmacology, 2018)
Glyceryl trinitrate (GTN) has found widespread use for the treatment of angina pectoris, a pathological condition manifested by chest pain resulting from insufficient blood supply to the heart. Metabolic conversion of GTN, a nitric oxide (NO) pro-drug, into NO induces vasodilation and improves blood flow. Patients develop tolerance to GTN after several weeks of continuous use, limiting the potential for long-term therapy. The mechanistic cause of nitrate tolerance is relatively unknown. We developed a cell culture model of nitrate tolerance that utilizes stable isotopes to measure metabolism of 15N3-GTN into 15N-nitrite. We performed global metabolomics to identify the mechanism of GTN-induced nitrate tolerance and to elucidate the protective role of vitamin C (ascorbic acid). Metabolomics analyses revealed that GTN impaired purine metabolism and depleted intracellular ATP and GTP. GTN inactivated xanthine oxidase (XO), an enzyme that is critical for the metabolic bioactivation of GTN into NO. Ascorbic acid prevented inactivation of XO, resulting in increased NO production from GTN. Our studies suggest that ascorbic acid has the ability to prevent nitrate tolerance by protecting XO, but not aldehyde dehydrogenase (another GTN bioactivating enzyme), from GTN-induced inactivation. Our findings provide a mechanistic explanation for the previously observed beneficial effects of ascorbic acid in nitrate therapy.